Determination of Hydrodynamic Dispersion Coefficient of Solute Transfort in Soil Using Inverse Problem Method - Hermantoro .; B. I. Setiawan (Jurnal Keteknikan Pertanian, 2002)
Solute transport in porous medium is affected by two parameters i.e : 1) average velocity of solute particle, and 2) solute dispersion. Theoretically, the solute transport can be describes by Convective Dispersion Equation, when the methods to determine D in this paper we present a modified method of inverse problem to calculate D. The results indicated that the inverse problem much or less matched with the analytical solution.